Role of Social Media in the 2016 Iowa Caucuses. Issue 3 (2nd October 2017) - Dimitrova, Daniela V.; Bystrom, Dianne
Abstract : Social media have become an indispensable tool in modern political campaigns, yet little is known about their impact, especially at the important primary and caucus stages of the US presidential elections. This study investigates the effects of visiting political party and candidate websites as well as following presidential candidates, posting political comments, and liking or sharing political content on social media on participation in the primary stage of the 2016 US election. The results of a precaucus survey in Iowa show that active use of social media tends to have positive effects, while passive social media use has a negative impact on likelihood of caucus attendance. Recommendations for campaigns include redirecting attention away from passive website viewing and developing social media content that will generate likes and shares.